Peran Gender dalam Pemanenan Hutan Kemiri Rakyat di Desa Barugae, Kecamatan Mallawa, Kabupaten Maros - Faradiba, Andi vika; Amaliah, Rizki (Jurnal Hutan dan Masyarakat, 2024)
The community candlenut forest in South Sulawesi is a community forest that was developed independently by the community. The hazelnut forest managed by the community in Maros Regency has been carried out since 1926. Farmers have managed and utilized candlenut plants from generation to generation as gardens that are physically equivalent to forests. The people's candlenut forest in Maros Regency has provided benefits both directly and indirectly. in the management of natural resources, community candlenut forest management involving community groups consisting of men and women allows for issues that arise as a result of differences based on gender. This study aims to analyze the roles of men and women in harvesting people's candlenut forests. The research was carried out in Barugae Village, Maros Regency, South Sulawesi Province in February-November 2022 with the process of collecting field data through observation, in-depth interviews, and FGD. The data obtained were then tabulated and processed and analyzed using gender analysis and descriptive analysis. The results of the study show that the division of roles between men and women in the management of the people's candlenut forest is different. Men do work that uses physical strength and is culturally identical to men's work, such as burning as a method of clearing land, making simple beds, clearing weeds, and planting and harvesting during the main harvest stage. Women who are attached to themselves with jobs related to the domestic sector not only take on the role of preparing for consumption, but also do the same work that is done by men, such as seeding, harvesting at the stages of subsequent harvests and makkalice, and drying and peeling candlenut seeds.